Towards an HCV vaccine: an overview of the immunization strategies for eliciting an effective B-cell response - Gabriel L. Costa; Giuseppe A. Sautto (Expert Review of Vaccines)
Introduction Fifty-eight million people worldwide are chronically infected with hepatitis C virus (HCV) and are at risk of developing cirrhosis and hepatocellular carcinoma (HCC). Direct-acting antivirals are highly effective; however, they are burdened by high costs and the unchanged risk of HCC and reinfection, making prophylactic countermeasures an urgent medical need. HCV high genetic diversity is one of the main obstacles to vaccine development. The protective role of the humoral response directed against the HCV E2 glycoprotein is well established, and broadly neutralizing antibodies play a crucial role in effective viral clearance.Areas covered This review explores the HCV targets and the different vaccination approaches, encompassing different expression systems, antigen selection strategies, and delivery methods, focusing on those aimed at eliciting a broad and effective humoral response. Our search criteria included the keywords ‘HCV,’ ‘Hepatitis C,’ and ‘vaccine’ using publicly available databases. Following the screening, 54 papers were selected.Expert opinion The investigation of novel vaccine platforms beyond traditional approaches is necessary. While progress has been made in this direction, continued investigations on the HCV virology, immunology, and vaccinology are essential to surmount associated obstacles, heling in the development of an HCV vaccine that can benefit the global public health.